2019
DOI: 10.1108/ijpdlm-10-2018-0358
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application supported urban-township e-grocery distribution

Abstract: Purpose The purpose of this paper is to present a mobile application supported townshipand urban e-grocery distribution models that uses a software application (app) to bridge the infrastructural barriers, costs and complexities associated with e-grocery delivery operations in rural township areas. Design/methodology/approach Using a qualitative multi-case approach and semi-structured interviews, the study explored distribution practices of eight national emerging e-grocery retail businesses to demonstrate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
(56 reference statements)
2
25
0
3
Order By: Relevance
“…There were reports of unavailability and substitutions, but they were quite minimal for the wholesale model. The insight supports Mkansi et al's (2020) findings on the moderate impact of unavailability issues on the e-grocery mobile application wholesale-configured model. In those instances of unavailability, customers were willing to take an alternative product, regardless of the price, because many orders were made by wealthy or well-to-do individuals on behalf of township families and communities.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There were reports of unavailability and substitutions, but they were quite minimal for the wholesale model. The insight supports Mkansi et al's (2020) findings on the moderate impact of unavailability issues on the e-grocery mobile application wholesale-configured model. In those instances of unavailability, customers were willing to take an alternative product, regardless of the price, because many orders were made by wealthy or well-to-do individuals on behalf of township families and communities.…”
Section: Discussionsupporting
confidence: 82%
“…We aim to re-launch in the next year". However, the e-grocers also witnessed increased competition from both small and big egrocery retailers, since the last interview with Mkansi et al (2020). For example, Shoprite Checkers, one of the biggest grocery retailers in South Africa launched Sixty60, an on-demand e-grocery mobile application with a value proposition beyond price, which is delivery of egroceries purchases within 60 minutes of order placement.…”
Section: Covid-19 Impact: E-grocery Mobile Application Ceo's Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest of analysing the e-grocery demand in a medium sized city is three-fold. Firstly, the e-grocery penetration is lower and customers' characteristics heavily differ from those in large cities [46]. Secondly, the transportation infrastructure is usually poorer than in large cities, which makes transportation activities less efficient [47].…”
Section: The E-grocery Demand Analysis In the City Of Pamplona (Spain)mentioning
confidence: 99%
“…And the results indicated that the convenience of goods changing and refunding, completeness of goods, pick-up appointment in advance, distribution cost are the utmost basic factors for sustainable last-mile delivery. Mkansi et al (2019) believed that insufficient resources and under-developed logistics infrastructure restrained the development of e-grocery logistics in townships and villages. Moreover, they developed an APP supported township and urban e-grocery distribution models to eliminate infrastructural barriers, costs, and complexities in rural township areas.…”
Section: Table 1 the Difference In Rural Last-mile Research Between Developing Countries And Developed Countriesmentioning
confidence: 99%